Nutritional status of Rohingya children in Kuala Lumpur - Teng, T. Sok; Mohd Shariff, Zalilah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2011)
The Rohingya is a group of refugees from Myanmar who have been residing in Malaysia since the 1980s. At present, there is no published information on health and nutritional status of refugee children in Malaysia. This study was conducted to assess nutritional status of the Rohingya children aged 6 months to 12 years old (N=87) and to determine the associations between nutritional status with socio-demographic, dietary diversity and health (birth weight, immunization and childhood illness) variables. Children were measured for weight and height while their guardians were interviewed for socio-demographic, dietary diversity and health information. About 27.5% of the Rohingya children were underweight, 11.5% stunted, 16.1% thin and 12.6% at risk of overweight and overweight. The percentage of children with low birth weight (< 2.5 kg) and no immunization was 17.8% and 11.5%, respectively. Fever (67.8%) and flu (62.1%) were the most common childhood illnesses reported in previous month with 44-75% of the children with these illnesses did not receive any medical treatment. The mean dietary diversity score was 8.9+3.2 out of a possible 14, with a higher score indicating a more diverse diet. There were significant correlations between frequency of immunization received by the children with weight-for-age-z score (rs=0.27, p<0.05), height-for-age-z score (rs=0.25, p<0.05) and BMI-for-age-Z score (rs=0.24, p<0.05). Height-for-age-z score was also positively correlated with childhood illness score (rp=0.24, p<0.05) and dietary diversity score (rp=0.23, p<0.05) in that children with less common childhood illnesses and variety of foods in the diets had better linear growth. As refugees have limited access to health care services, they are at greater risk of health and nutritional problems.